Photoacoustic Method as a Tool for Analysis of Concentration-Dependent Thermal Effusivity in a Mixture of Methyl Alcohol and Water - PONIKWICKI, Nikodem; SZCZEPANIK, Łukasz; GONDEK, Joanna; LINDE, Bogumił B.J.; SKRODZKA, Ewa Barbara; MOLCHANOV, Vladimir; YUSHKOV, Konstantin B.; GRECHISHKIN, Rostislav (Archives of Acoustics, 2019)
It has been shown in the present paper that exploitation of the experimental potential of a photoacoustic technique can provide information on a type of intermolecular interactions in aqueous mixtures containing organic liquids, when the basic parameters of these mixtures, such as density, ρ, specific heat, cp, or thermal conductivity, λ, are unknown. Earlier investigations of concentration dependence of effusivity in different aqueous solutions of organic liquids demonstrated that the photoacoustics method is a sensitive tool to identify hydrophobic properties of such liquids. In our experiment this suggestion was exploited for a solution of methanol which is known to display much weaker hydrophobicity than other alcohols. It was confirmed that the location of extreme deviations from linearity for the thermal effusivity, Δe, agrees well with that of characteristic points for the isentropic compressibility coefﬁcient, κS, and the excess molar volume, VEm, as a function of the concentration.